1-Quasiconformal Mappings and CR Mappings on Goursat Groups - Qing Yan Wu; Zun Wei Fu (The Scientific World Journal)
We show that 1-quasiconformal mappings on Goursat groups are CR or anti-CR mappings. This can reduce the determination of 1-quasiconformal mappings to the determination of CR automorphisms of CR manifolds, which is a fundamental problem in the theory of several complex variables.